Inquiry: Teaching And Learning Children With Special Needs - Kholisna, Titin; Baharuddin, Ferry (Jurnal Simki Pedagogia, 2023)
Children with special needs are children who have special characteristics and are different from other children. Students who have needs in teaching and learning require ways or methods and strategies as well as specially prepared media.The aims research is to describe a situation, condition and activities of teachers and students with special needs that are housed in the MB3+ Sidotopo Kepanjen, Kab. Malang. This research method uses a descriptive qualitative approach with inquiry uncovering, understanding, examining the contextual meaning of an object based on the participant's point of view from the findings in the field. The result analysis technique is by reducing, presenting and verifying the data. Sources of data were obtained from teachers, students, guardians, documentation and participating in activities at school. The results showed several types of children with special needs including autism, speech delay, deaf, speech impaired, mental retardation with a total of 20 students at the age of 3 years to 15 years. Teaching here uses methods and strategies including communication, assignments, instructions, prompts, cooperation, and creative programs that support the progress of child development.